The immune tolerance role of Bregs in inhibiting human inflammatory diseases, with a focus on diabetes mellitus - Zhang, Qi; Liao, Jinfeng; Liu, Zheng; Song, Siyuan; Tian, Limin; Wang, Yi (Frontiers in Immunology, 2025)
Regulatory B cells (Bregs) are pivotal modulators of immune tolerance, suppressing inflammation through cytokine secretion and cellular interactions. Their role is particularly significant in inflammatory diseases such as type 1 and type 2 diabetes mellitus (T1DM and T2DM), where immune dysregulation contributes to disease progression. In T1DM, Bregs mitigate β-cell autoimmunity via IL-10 production and FOXP3-mediated pathways, but genetic mutations and dysfunctions in these mechanisms exacerbate autoimmunity. In T2DM, chronic inflammation and metabolic stress impair Breg numbers and function, further fueling insulin resistance. While Bregs play a central role in T1DM by directly preventing β-cell destruction, their role in T2DM is more supportive, modulating inflammation in metabolically stressed tissues. Emerging therapeutic strategies aim to enhance Breg function through IL-10 induction, ex vivo expansion, or targeting Breg-specific pathways using gene-editing and small molecules. Future research should explore Breg heterogeneity, novel markers, and personalized therapies to unlock their full potential. Understanding and leveraging the immune tolerance role of Bregs may offer transformative strategies to inhibit inflammatory diseases like diabetes mellitus.